PENINGKATAN KEMATANGAN KARIER MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING DAN PENGGUNAAN BOARD GAME CAREER RACING PADA PESERTA DIDIK KELAS XII: Penerapan Model Problem Based Learning dan Penggunaan Board Game Career Racing Dalam Peningkatan Kematangan Karier Peserta Didik - Kristin, Firosalia; Tritjahjo Danny Soesilo; Yustinus Windrawanto; Aurellia Jeslyn; Adi Nurhidayat (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2025)
Many high school students lack certainty in determining their future careers after graduation. This quasi-experimental study examined the significant improvement in career maturity of grade 12 students through the application of Problem-Based Learning (PBL) and the use of a career guidance board game,